A Review of the Natural History of Chronic Hepatitis C Infection - Wilder, Julius; Patel, Keyur (North American Journal of Medicine and Science, 2014)
The burden of chronic hepatitis C infection worldwide is significant. Approximately 4.1 million people in the United States have anti-HCV antibodies. The prevalence worldwide varies, but reaches greater than 3.5% in some regions (North African, East Asia). The burden of hepatitis C virus is reflected in the morbidity and mortality of this disease, as well as the societal costs. The morbidity and mortality associated with chronic hepatitis c infection is mostly related to the rate of fibrosis and associated progression to cirrhosis. The natural history of this progression is a complex and dynamic process related to individual characteristics (age, sex, race, genetics), viral characteristics (genotype), behavioral (smoking, alcohol), metabolic factors (insulin resistance, obesity), and co-infection (Hepatitis B and HIV). This review describes the current literature on how these factors interact with chronic hepatitis C infection and impact the natural history of this disease and progression to fibrosis and cirrhosis.